Polityka kredytowa przedsiębiorstw w świetle badań empirycznych - Bera, Anna (Credit Policy of Enterprises in the Light of Empirical Research, 2006)
The article presents the essence and the reasons of the trade credit. The presentation and the assessment of particular aspects of the credit policy in Polish companies is described in this article which concentrates especially on the trade credit strategy, the volume of the credit sale, the level of past due payments and uncollectible and also on the basic instruments of credit policy and security methods. The research has been prepared based on the questionnaire sent to the group of 81 companies from north-western Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 54-64